Becoming a citizen through marriage: How gender, ethnicity and class shape the nation - Kristol, Anne; Dahinden, Janine (My University, 2020)
The role of marriage in accessing membership entitlements has been studied extensively in the context of marriage migration, but it remains under-researched in the literature on citizenship acquisition. This paper explores specific constructions of deservingness vis-à-vis the foreign spouses of citizens and their marriages in the context of facilitated naturalization in Switzerland. Based on an ethnographic investigation of the naturalization practices of street-level bureaucrats, we show that the politics of belonging in the context of access to citizenship is regulated by intersecting gendered, ethnicized and classed logics of desirability about how a marriage should be. Additionally, a patrilineal logic continues to guide street-level bureaucrats de facto even when legislation has introduced de jure gender equality. Finally, we demonstrate that it is not only immigration regimes, but also citizenship regimes that employ assumptions about what constitutes a ‘good marriage’ in order to draw the boundaries of the nation.
Keywords: gender; citizenship; street-level bureaucrats; nation-state; marriage; politics of belonging